Efficacy of Foot and Ankle Corticosteroid Injections. (January 2017) - Grice, John; Marsland, Daniel; Smith, George; Calder, James
Background: Corticosteroid injections have been used for a variety of foot and ankle pathologies over the years, and our aim was to evaluate the efficacy and safety of them in our clinic. Materials and Methods: We performed a retrospective review of notes and a telephone questionnaire on the clinical outcome of all patients who underwent a corticosteroid injection of the foot or ankle in a year. All procedures were performed in an outpatient setting by a consultant musculoskeletal radiologist using either ultrasound or X-ray guidance and had a minimum of 2 years of follow-up. Results: Overall, 314 of 365 (86%) patients reported a significant improvement in symptoms, and 242 (66%) reported complete resolution of their pain, with 107 (29%) remaining asymptomatic at the 2-year follow-up. The mode time of recurrence of pain was 3 months. Fifty-one (14%) underwent a further injection and 88 (24%) underwent operative intervention within the follow-up period. Complication rates in our series were low. There were no reported infections. Complications occurred in 5 patients (1.3%), including steroid flare, pain, and plantar plate ruptures. Conclusion: Corticosteroid injections were a safe and effective option for treating a variety of foot and ankle conditions and reduced the need for surgery. They were particularly effective for the treatment of ankle soft tissue impingement. They appear ineffective in providing significant improvement in pain for longer than 3 months in conditions such as plantar fasciitis and hallux rigidus. Level of Evidence: IV, case series.